2005
DOI: 10.1152/ajplung.00125.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of ozone on THP-1 cells in response to SP-A stimulation

Abstract: , a major component of air pollution and a strong oxidizing agent, can lead to lung injury associated with edema, inflammation, and epithelial cell damage. The effects of O 3 on pulmonary immune cells have been studied in various in vivo and in vitro systems. We have shown previously that O 3 exposure of surfactant protein (SP)-A decreases its ability to modulate proinflammatory cytokine production by cells of monocyte/macrophage lineage (THP-1 cells). In this report, we exposed THP-1 cells and/or native SP-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 83 publications
(104 reference statements)
0
26
0
2
Order By: Relevance
“…We and others have identified macrophage-derived mediators present in the lung after ozone exposure (27, 28). However, this observation remains somewhat inconsistent and may be dependent on the intensity and duration of exposure, as other groups have demonstrated that ozone exposure results in a decrease in macrophage-derived cytokines (2931). Macrophages can also serve a protective role in the setting of ozone-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have identified macrophage-derived mediators present in the lung after ozone exposure (27, 28). However, this observation remains somewhat inconsistent and may be dependent on the intensity and duration of exposure, as other groups have demonstrated that ozone exposure results in a decrease in macrophage-derived cytokines (2931). Macrophages can also serve a protective role in the setting of ozone-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the levels of oxidized SP-A, and specifically the levels of the dimeric form of SP-A, were significantly higher in FA-exposed, infected female mice compared to their male counterparts. Whether this is a consequence of a robust macrophage antimicrobial activity (as suggested above for the oxidation of total BAL protein) resulting in SP-A functional deficits [20,23,25,35] or whether the oxidized dimeric form mediates important signaling pathways is not known. However, SP-A and some other proteins (as proposed by us and others) may serve as sacrificial antioxidants [33,36-39].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative differences include differences between the SP-A1 and SP-A2 genes and/or variants in basal mRNA levels and in response to dexamethasone (22,33,48,58) and in protein levels in bronchoalveolar lavage (BAL) fluids from different individuals (52). Mechanisms involving NF-B activation (21,28) and mRNA stability and translational control (57) may contribute to quantitative differences.…”
mentioning
confidence: 99%
“…Ozone-induced oxidation of SP-A reduces its ability to interact with alveolar macrophages (AMs; Ref. 46), inhibits phosphatidylcholine secretion from alveolar type II cells (45,56), and has an impact on cytokine production in THP-1 cells (61) via ineffective activation of the NF-B cell signaling pathway (21). After ozone exposure of SP-A, its aggregation pattern, absorption spectra, gel electrophoretic pattern (50,56), and SP-A-dependent extracellular surfactant morphology (45,46) are also changed.…”
mentioning
confidence: 99%